2016
DOI: 10.1080/08927022.2016.1139108
|View full text |Cite
|
Sign up to set email alerts
|

To keep or not to keep? the question of crystallographic waters for enzyme simulations in organic solvent

Abstract: The use of enzymes in non-aqueous solvents expands the use of biocatalysts to hydrophobic substrates, with the ability to tune selectivity of reactions through solvent selection. Non-aqueous enzymology also allows for fundamental studies on the role of water and other solvents in enzyme structure, dynamics, and function. Molecular dynamics simulations serve as a powerful tool in this area, providing detailed atomic information about the effect of solvents on enzyme properties. However, a common protocol for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Our previous work addressed the question of keeping (or not keeping) crystallographic water molecules in simulations of enzymes, and we found that slowly-diffusing waters in organic solvent should be kept in order for simulations to quickly equilibrate (as described in Methods). We also saw that the location of retained waters affects conformational sampling (Dahanayake et al, 2016 ). We have postulated that both buried and slow-diffusing water molecules are the ones which are retained experimentally when enzymes are used in organic solvent.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our previous work addressed the question of keeping (or not keeping) crystallographic water molecules in simulations of enzymes, and we found that slowly-diffusing waters in organic solvent should be kept in order for simulations to quickly equilibrate (as described in Methods). We also saw that the location of retained waters affects conformational sampling (Dahanayake et al, 2016 ). We have postulated that both buried and slow-diffusing water molecules are the ones which are retained experimentally when enzymes are used in organic solvent.…”
Section: Discussionmentioning
confidence: 80%
“…The starting coordinates of CALB enzyme were taken from the X-ray crystallographic structure (PDB ID: 1TCA). Six buried crystallographic water molecules identified by Uppenberg et al ( 1994 ) were kept, as it was concluded in our previous studies (Dahanayake et al, 2016 ) that this leads to fastest equilibration in non-aqueous simulations. All the simulations were performed using GROMACS (version 4.6.3) (Kamatari et al, 1996 ) software package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results show that the nature of organic solvents influences the extent of stripping of water molecules from the protein surface: non-polar solvents give rise to tightly bound large water clusters on the protein surface, while polar solvents promote loosely bound small clusters of water [ 136 ]. A recent MD simulation study of Candida antarctica lipase B (CALB) and cytochrome c enzymes indicates that retaining buried waters in the presence of different non-aqueous solvents leads to faster-equilibrating MD trajectories [ 138 ]. Furthermore, retaining buried waters affects the conformational sampling of CALB in organic solvents.…”
Section: Effect Of Small Molecule Interactions On Protein Structurmentioning
confidence: 99%
“…An atomistic MD docking simulation of the P450BM-3 heme domain was performed to investigate preferential binding modes and electron transfer (ET) from an ET mediator, cobalt(II) sepulchrate (Co(II)Sep), to the heme iron in solution at different Co(II)Sep concentrations [ 138 ]. Results provided new insights into the ligand adsorption mechanism, through detailed binding site mapping on the protein surface.…”
Section: Effect Of Small Molecule Interactions On Protein Structurmentioning
confidence: 99%